Modified Nano-Perovskite Catalysts for the Steam and CO2 Reforming of Methane - Park, Daeil; Moon, Dong Ju; Bae, Jong Wook; Kim, Taegyu (AMER SCIENTIFIC PUBLISHERS, 2015)
This paper describes the synthesis and characterization of La0.8Sr0.2NiO3 nano-perovskite type catalyst for steam-CO2 reforming (SCR) and CO2 reforming (DR) of methane. Effect of gelation agents such as PVA, EDTA and PAA on nano-perovskite structures was investigated. XRD, H-2-TPR and FT-IR analysis were used to characterize the prepared catalysts. The catalytic reaction was performed in a fixed bed reactor system at 1 atm and 800 degrees C. The feed ratio of CH4:H2O:CO2 as reactants was adjusted according to the SCR and DR reactions. As a result, CH4 and CO2 conversions of PVA agent catalyst were higher than that of PAA and EDTA agent catalyst for DR reaction because the PVA agent catalyst had a well-established perovskite, a high absorption, a high reducibility. However, the PAA agent catalyst had a higher reactivity due to its high interaction of catalysts for SCR of methane due to its strong interaction of Catalysts.